'I Was Close to Them': Re-experiencing War through Trauma-based Interviews. (2nd January 2020) - Jeftić, Alma
ABSTRACT: Previous scholarly work on vicarious trauma provides an overview of how researchers have been personally coping with the hazards of their work. In order to understand the deep meanings of war and genocide, researchers end up being caught between representations of reality and their personal reflexions on it. In this paper I will elaborate on vicarious tortures for already traumatized researchers; hence, my attempt is to enlighten the position of researcher – war survivor who conducts the research on war trauma. Using an example of my own research, I will analyze the process of dealing with the trauma in a situation in which both the researcher and the respondents experienced the same war. Becoming aware of emotional and bodily reactions to the events I explored together with my participants I started finding personal traumatic experiences that existed parallel to the experiences reported by participants. In this paper, I attempt to define the context, development and purpose of 'finding a parallel narrative and emotion' and the importance of active listening and empathy throughout that process. Also, how my traumatic experiences influenced my participants' narratives of the traumatic past and vice versa will be explored as one of the enlightening processes emerging from fieldwork.